Effect of INM on Growth and Yield of Capsicum (Capsicum annuum l.) under Protected Cultivation - Shubham Sharma; Vinay Joseph Silas; Jitendra Kumar; Raghvendra Singh; Ravikesh Kumar Pal; Anushka Tripathi; Dilip Kumar (Archives of Current Research International, 2025)
The present investigation entitled "Effect of INM on Growth and Yield of Capsicum (Capsicum annuum L.) Under Protected Cultivation" was conducted at the Horticulture Research Farm, Faculty of Agricultural Sciences and Allied Industries, Rama University, Kanpur (U.P.) during 2024–2025. The experiment comprised nine treatments, replicated thrice in a randomized block design (RBD). It was concluded that the application of integrated nutrient management (INM) had a significant effect on almost all the growth, yield, and quality parameters of capsicum. The results revealed that the maximum plant height (79.84 cm), number of branches per plant (18.13), number of leaves per plant (94.65), leaf area (164.34 cm²), days to 50% flowering (35.38), number of flowers per plant (18.37), number of fruits per plant (15.37), fruit length (8.07 cm), fruit diameter (7.09 cm), fruit weight (72.61 g), pericarp thickness (9.17 mm), fruit yield per plant (1.116 kg), fruit yield per plot (16.74 kg), fruit yield per hectare (34.87 t ha⁻¹), total soluble solids (6.83 °Brix), and ascorbic acid content in fruit juice (150.93 mg/100g) were recorded with treatment T7 (50% FYM + 25% NPK + 25% Vermicompost). In terms of economics, treatment T7 (50% FYM + 25% NPK + 25% Vermicompost) also recorded the highest gross return (Rs. 15,69,033.3 ha⁻¹), net return (Rs. 13,43,532.9 ha⁻¹), and benefit-cost ratio (1:5.96).